Aerial CO2 Trapped as CO32– Ions in a Dimeric Capsule That Efficiently Extracts Chromate, Sulfate, and Thiosulfate from Water by Anion‐Exchange Metathesis. Issue 25 (21st July 2014) - Dutta, Ranjan; Chakraborty, Sourav; Bose, Purnandhu; Ghosh, Pradyut
Abstract: The tris(2‐aminoethyl)amine‐based (tren‐based) 3‐cyanophenyl‐substituted tripodal ureaL1, one of the familiar urea‐based anion receptors, has shown encapsulation of CO3 2– ions as the carbonate capsule [(L1 )2 · (CO3 )· (TBA)2 ] (1, TBA = tetrabutylammonium) by the fixation of aerial carbon dioxide from basic dimethyl sulfoxide (DMSO) solution. Single‐crystal X‐ray structural analysis confirmed the encapsulation of CO3 2– ions in the cavity of a dimeric capsular assembly ofL1 (9.62 Å) through the formation of twelve strong N–H··· O hydrogen‐bonding interactions. The excellent CHCl3 and CH2 Cl2 solubility of1 has been exploited for the liquid–liquid (L–L) extraction of CrO4 2–, SO4 2–, and S2 O3 2– ions from water by anion‐exchange metathesis. The extraction of these anions from water was unambiguously confirmed by 1 H NMR spectroscopy, IR spectroscopy, powder XRD (PXRD), and single‐crystal X‐ray diffraction analysis. The 1 H NMR spectroscopic analysis of the bulk extracts supports the formation of 2:1 (host–guest) complexes. For the CrO4 2– ion, the 53 Cr NMR spectrum of the bulk extract shows a characteristic peak at δ = –99.98 ppm. The complexes of CrO4 2–, S2 O3 2–, and SO4 2– ions withL1 (i.e., 2 –4, respectively) were obtained from crystallization of the bulk extracts and show anion‐assisted dimeric capsular assemblies ofL1 through multiple N–H··· X (X = O, S) interactions. The dimensions of the anion‐encapsulated capsular assemblies are quite similar to that of the carbonate capsule and are 9.70 Å for [(L1 )2 · (CrO4 )· (TBA)2 ] (2 ), 9.61 Å for [(L1 )2 · (S2 O3 )· (TBA)2 ] (3 ), and 9.71 Å for [(L1 )2 · (SO4 )· (TBA)2 ] (4 ). Quantification by weighing the bulk extract shows that1 can separately extract ca. 90 % of the above three anions from water by anion‐exchange metathesis. The quantitative estimations of the extractions of SO4 2– and CrO4 2– ions were further verified by gravimetric analysis by BaSO4 and BaCrO4 precipitation techniques, respectively. The extraction of SO4 2– ions from water was also demonstrated under alkaline conditions (pH 12.5) and in the presence of an excess of nitrate ions. Further, the quantification of CrO4 2– extraction was established by solution‐state UV/Vis studies. Abstract : In the solid state, a tripodal urea receptor encapsulates CO3 2– ions in its dimeric capsular assembly, which is further exploited for the liquid–liquid (L–L) extraction of CrO4 2–, S2 O3 2–, and SO4 2– ions from water. Different spectroscopic techniques and X‐ray diffraction studies confirm the efficient extraction of these environmentally relevant anions.